Knowledge of nursing students on the teaching-learning Systematization of Nursing Care - Andrade, Yara Nayá Lopes de; Menezes, Elielza Guerreiro; Jardim, Mara Julyete Arraes; Ribeiro, Jéssica Sâmia Silva Tôrres; Chaves, Rodson Glauber Ribeiro; Rolim, Isaura Letícia Tavares Palmeira (Rev Rene, 2016)
Objective: to analyze the knowledge of nursing students about the teaching-learning process of the Systematization of Nursing Care. Methods: this is a cross-sectional analytical research type, carried out with 111 students of the Nursing undergraduate course through a form. The calculation of the statistical frequencies and percentages was performed for the analysis. Results: 42.0% reported the use of traditionalist teaching methodology. 54.9% consider that the greatest difficulty was to relate theory and practice. 34.3% reported the case of partial lack of interest of students. 33.3% indicated methodological divergence of teachers. Conclusion: the main difficulty of the academics surveyed in the teaching-learning process occurred by the gap between the theoretical knowledge and practical applicability, together with the form of predominantly traditionalist education.